Peningkatan Keterampilan Menulis Hanzi Melalui Pemanfaatan Website Writechinese.Com Pada Peserta Didik Kelas XI SMK Ketintang Surabaya Tahun Ajaran 2025/2026 - Ardhiani , Aisyah; Masrur, Muhammad Farhan (JURNAL MANAJEMEN PENDIDIKAN, 2026)
IMPROVING HANZI WRITING SKILLS THROUGH THE USE OF THE WRITECHINESE.COM WEBSITE FOR GRADE XI STUDENTS OF SMK KETINTANG SURABAYA IN THE 2025/2026 ACADEMIC YEAR Students at SMK Ketintang Surabaya experience difficulties in learning to write Chinese characters. This condition indicates the need for the implementation of technology-based learning media, one of which is through the use of the WriteChinese.com website. This study aims to determine the use of the WriteChinese.com website, its effectiveness in learning to write Chinese characters, and to determine students' responses to the media. This study uses a quantitative approach with an experimental research type and True Experimental Design. The research subjects were 72 students of grade XI who were divided into a control class and an experimental class. The data collection process was carried out through observation, tests (pretest and post-test), and questionnaires. The test data were analyzed using the t-test formula using SPSS Statistics 25. The results showed that the average post-test score of the experimental class was higher than the control class. Based on the calculations that have been done, the calculated t value was 8.17 with d_b = 70 at a significance level of 0.05. It is known that the t-table value is 1.994, so the calculated t is greater than the t-table (8.17 ≥ 1.994). Based on these results, it can be concluded that the use of the WriteChinese.com website has a significant influence on students' hanzi writing skills.